An analysis of five negative sprite‐parent discharges and their associated thunderstorm charge structures. Issue 2 (26th January 2016) - Boggs, Levi D.; Liu, Ningyu; Splitt, Michael; Lazarus, Steven; Glenn, Chad; Rassoul, Hamid; Cummer, Steven A.
Abstract: In this study we analyze the discharge morphologies of five confirmed negative sprite‐parent discharges and the associated charge structures of the thunderstorms that produced them. The negative sprite‐parent lightning took place in two thunderstorms that were associated with a tropical disturbance in east central and south Florida. The first thunderstorm, which moved onshore in east central Florida, produced four of the five negative sprite‐parent discharges within a period of 17 min, as it made landfall from the Atlantic Ocean. These negative sprite‐parents were composed of bolt‐from‐the‐blue (BFB), hybrid intracloud‐negative cloud‐to‐ground (IC‐NCG), and multicell IC‐NCGs discharges. The second thunderstorm, which occurred inland over south Florida, produced a negative sprite‐parent that was a probable hybrid IC‐NCG discharge and two negative gigantic jets (GJs). Weakened upper positive charge with very large midlevel negative charge was inferred for both convective cells that initiated the negative‐sprite‐parent discharges. Our study suggests tall, intense convective systems with high wind shear at the middle to upper regions of the cloud accompanied by low cloud‐to‐ground (CG) flash rates promote these charge structures. The excess amount of midlevel negative charge results in these CG discharges transferring much more charge to ground than typical negative CG discharges. We find that BFB discharges prefer an asymmetrical charge structure that brings the negative leader exiting the upper positive charge region closer to the lateral positive screening charge layer. This may be the main factor in determining whether a negative leader exiting the upper positive region of the thundercloud forms a BFB or GJ. Key Points: Negative sprite‐parent lightning forms in tall, intense convective cells with low CG flash rates BFBs, hybrid IC‐NCGs, and multicell IC‐NCGs are negative sprite‐parent lightning types BFB discharges prefer an asymmetrical charge structure